Analysis of Shape Control Characteristics for UCMW Cold Rolling Mill Non-Oriented Silicon Steel - Hao Tao (Metals, 2020)
In order to analyze the flatness control characteristics for a certain UCMW (Universal Crown Mill with Work roll shifting) cold rolling mill, combined with the actual parameters in the field, a static simulation model of the quarter roll systems of the UCMW cold rolling mill was established by the ANSYS finite element software. The bearing roll gaps under the factors of the unit width rolling force, the roll bending force and the roll shift were calculated, which reflects the shape control characteristics and has a great influence on the friction and lubrication characteristics between the roll gaps. Additionally, the shape control strategy of the process parameters in the field was put forward. The results show that, at first, the work roll shift is the most effective shape control means, while the current-used range of the intermediate roll shift cannot make full use of the roll end contour of the intermediate roll, so the intermediate roll negative shift should be considered for shape control. At second, the excessive rolling force goes against the shape control, so the rolling force of each stand should be reasonably distributed. Finally, the shape control ability of the bending force is relatively weak, so the range of the work roll bending force should be appropriately increased.